Rebel-to-party transformations in civil war peace processes 1975–2011. Issue 2 (18th September 2016) - Söderberg Kovacs, Mimmi; Hatz, Sophia
ABSTRACT: Previous research has established the critical relevance of better understanding the conditions that either facilitate or obstruct rebel-to-party transformations for the sake of strengthening the prospects for both peace and democracy in post-war societies. In this study, we contribute to this growing research agenda in two ways. We first present and analyse data collected by the Uppsala Conflict Data Program (UCDP) on all peace agreements that contain specific rebel-to-party provisions during the time period 1975–2011. Second, we introduce new data on rebel-to-party outcomes during the same time period. The descriptive findings confirm several of our theoretical expectations. Rebel-to-party provisions are exclusive to the post-Cold War era, and are commonly included in peace agreements with third-party presence. Somewhat surprisingly, we have seen almost twice as many agreements with such provisions in Africa compared to other regions, and only in peace agreements in governmental conflicts. However, we find several cases of rebel-to-party outcomes in territorial conflicts. Our data also confirm that rebel-to-party provisions are neither necessary nor sufficient for rebel-to-party outcomes, and highlight the potential relevance of other political provisions also supporting the group's political integration.